Efektivitas Metode Presentasi dalam Pembelajaran terhadap Pengembangan Nalar Kritis Mahasiswa: Studi Kualitatif - Fadhil Ikhsan Nur Ramadhan; Risky Fajriyatuz Zahro (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the effectiveness of presentation-based learning in developing students’ critical thinking skills. This research uses a qualitative approach with a descriptive method. The subjects of this study were five students who participated in presentation-based learning. Data were collected through in-depth interviews and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The results show that presentation-based learning is the dominant method used in the classroom; however, it has not been fully effective in developing students’ critical thinking. This is indicated by low student participation, limited understanding of the material, and lack of interaction during the learning process. Therefore, more optimal learning management is needed to improve the quality of education.